A study of psychological impact of COVID-19 pandemic and lockdown in India: An online survey - Vivek B. Waghachavare; Alka D. Gore; Sheetu Maharaj K. Jailkhani; Randhir V. Dhobale; Girish B. Dhumale (Al Ameen Medical College, 2021)
Background: The COVID-19 pandemic has created an unparalleled challenge resulting in millions of cases and lakhs of deaths. It has taken a large toll on people, health systems and economies. Also, the prolonged lockdown imposed following COVID-19, poses a challenge to the people's psychological health. Objectives: The objectives of this research were to study the awareness regarding COVID-19 pandemic, impact of nationwide lockdown among the people and influence of these factors in the development of stress, anxiety, and depression. Methods: An online cross-sectional study was conducted from 12th to 18th April 2020, using Google forms on social media. Participants were recruited using snowball sampling method. Appropriate ethical approval and consents were acquired. Analysis was done usingSPSS-22, applying percentages, chi-square test and regression analysis. Results: Of 517 participants, 229 (44.3%) and 443 (85.7%) had good knowledge regarding COVID-19 and desirable preventive practices, respectively. One hundred eighty-one (35%) participants were severely impacted due to lockdown, and it was a significant predictor of stress, anxiety, and depression. Conclusion: The situation created due to lockdown may have a negative impact on mental health of the people and needs further assessment.